2020
DOI: 10.3390/diagnostics10090698
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral White Matter Lesions on Diffusion-Weighted Images and Delayed Neurological Sequelae after Carbon Monoxide Poisoning: A Prospective Observational Study

Abstract: Introduction: Carbon monoxide (CO) poisoning can result in delayed neurological sequelae (DNS). Factors predicting DNS are still controversial. This study aims to determine whether acute brain lesions observed using diffusion-weighted magnetic resonance imaging (MRI) following acute CO poisoning are related to the subsequent development of DNS. Methods: This prospective study was conducted on patients with CO poisoning treated at a university hospital in Bucheon, Korea. From August 2016 to July 2019, a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Exposures included carbon monoxide (29 studies, n = 1,409; 28 studies/ n = 1,373 in meta‐analysis), 15–43 carbon disulfide (4 studies, n = 797; 3 studies/ n = 131 in meta‐analysis), 44–47 1,2‐dichloroethane (4 studies, n = 40, n = 40 in meta‐analysis), 48–51 toluene (4 studies, n = 64/ n = 64 in meta‐analysis), 52–55 diving (4 studies, n = 266; 4 studies/ n = 172 in meta‐analysis), 56–59 high altitude (11 studies, n = 950; 5 studies/ n = 164 in meta‐analysis), 60–70 contact sports (3 studies, n = 629; not meta‐analyzable), 71–73 lead (2 studies, n = 423, not meta‐analyzable), 74,75 military (10 studies, n = 18,893, not meta‐analyzable), 76–85 pesticides/fertilizers (1 study, n = 8623, not meta‐analyzable), 86 miscellaneous solvents (4 studies, n = 251, not meta‐analyzable), 87–90 and broad occupational categories in population‐based dementia studies (9 studies, n = 15,118, not meta‐analyzable) 91–99 …”
Section: Resultsmentioning
confidence: 99%
“…Exposures included carbon monoxide (29 studies, n = 1,409; 28 studies/ n = 1,373 in meta‐analysis), 15–43 carbon disulfide (4 studies, n = 797; 3 studies/ n = 131 in meta‐analysis), 44–47 1,2‐dichloroethane (4 studies, n = 40, n = 40 in meta‐analysis), 48–51 toluene (4 studies, n = 64/ n = 64 in meta‐analysis), 52–55 diving (4 studies, n = 266; 4 studies/ n = 172 in meta‐analysis), 56–59 high altitude (11 studies, n = 950; 5 studies/ n = 164 in meta‐analysis), 60–70 contact sports (3 studies, n = 629; not meta‐analyzable), 71–73 lead (2 studies, n = 423, not meta‐analyzable), 74,75 military (10 studies, n = 18,893, not meta‐analyzable), 76–85 pesticides/fertilizers (1 study, n = 8623, not meta‐analyzable), 86 miscellaneous solvents (4 studies, n = 251, not meta‐analyzable), 87–90 and broad occupational categories in population‐based dementia studies (9 studies, n = 15,118, not meta‐analyzable) 91–99 …”
Section: Resultsmentioning
confidence: 99%
“…Prominent and bright signal changes in abnormal lesions are evident on MRI, reflecting a series of damage caused by COP-induced ischemic changes. Additionally, the morphology, asymmetry, and location of the lesion must be determined 16 , 26 . Previous studies demonstrated that the globus pallidus structure represents the best area to observe abnormalities in patients with acute COP 5 , 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Positive lesions in routine MRI scanning can be found in CO poisoning patients with severe brain injury, such as abnormally high signals on the DWI sequence, and research suggests that such patients often have a poor prognosis 10 . To verify that patients who did not find lesions on routine MRI images also had changes in functional brain networks, we organized three neurologists (W.Z., 30 years of research experience; H.Z., 10 years of research experience; G.Z., 7 years of research experience) to confirm the routine MRI images of all patients through visual examinations and excluded patients who found positive lesions, and repeated the network analysis with the remaining patients.…”
Section: Methodsmentioning
confidence: 99%
“…Routine MRI is the preferred examination method for detecting brain injury after CO poisoning and has the advantages of being noninvasive and convenient, but it has certain limitations in detecting and quantifying microscopic lesions in the brain and reflecting the severity and prognosis of the disease 10 . Resting‐state MRI (fMRI) indirectly reflects the activity of brain regions and blood oxygen level‐dependent (BOLD) signal fluctuations 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation